Fostering inclusive learning through bilingual drama-based storytime and UDL for young emergent multilinguals with disabilities - Sultan Kilinc; Nikkia D. Borowski; Jenny Millinger; Michael F. Kelley (Journal of Childhood, Education & Society)
This study explores how drama-based storytime lesson activities in two dual-language bilingual education (DLBE) developmental preschool classrooms serving emergent multilinguals with disabilities (EMwDs) align with Universal Design for Learning (UDL) principles. Traditional, one-size-fits-all educational practices often create barriers for diverse learners, including young EMwDs, by designing lessons for an “average” student. Drama-Based Pedagogy (DBP), which integrates drama strategies into academic instruction, has been shown to support young children’s language, literacy, and socioemotional development, particularly in early childhood settings. Similarly, UDL focuses on removing barriers to learning by designing instruction that accounts for learner variability through three key principles: representation, engagement, and action and expression. We argue that DBP and UDL offer complementary approaches that embrace learner diversity and promote inclusive, responsive, and accessible learning environments. This study was conducted as part of a larger professional development program designed to prepare early childhood teachers to integrate drama strategies into literacy instruction in DLBE classrooms. We analyzed drama-based storytime activities led by a drama teaching artist and a preschool educator in morning and afternoon developmental preschool DLBE classrooms, serving ten EMwDs. Using Vosaic software, we deductively analyzed 18 videotaped drama lessons. Findings revealed that drama-based storytime lessons align with UDL’s principles of representation, engagement, and action and expression, while also creating unique opportunities for EMwDs to have their abilities recognized and to actively participate through multiple modalities in English and Spanish storytime lessons.